Malignant primitive epithelioid sarcoma with features of rhabdoid tumor presenting in utero with diffusely metastatic disease - Christina M. Theodorou; Erin G. Brown; Payam Saadai; Shinjiro Hirose; Diana L. Farmer (Elsevier, 2020)
Diagnosis of a tumor in utero is a rare occurrence and poses diagnostic and therapeutic challenges. In cases of tumor-associated hydrops, there is significant risk of fetal demise, and prenatal intervention may be considered to avoid this outcome when possible. When fetal intervention is unlikely to improve survival, information can be useful for counseling families. We present a rare case of fetal diagnosis of a primary renal malignancy with widespread metastases and hydrops, with unique immunohistochemical findings consistent with malignant primitive epithelioid sarcoma with features of rhabdoid tumor.